TRACE ELEMENTS ANALYSIS OF CROPS AND VEGETABLES GROWN AROUND INDUSTRIAL AREAS OF FAISALABAD AND GUJRANWALA CITIES USING INAA AND AAS - Husaini, S. N.; Ullah, Mati; Akram, M.; Zaidi, J. H.; Subhan, K. (The Nucleus, 2010)
Industrial effluents pollution is a source of risk to the health of people living in industrial cities of Pakistan. Most of the untreated effluents are discharged to the nearby agricultural fields that pollutes the vegetation grown in such soil. A majority of the industries are not equipped with suitable recycling and effluent treatment plants. Consequently, toxic metals enter our food chain and results in significant health risks and serious diseases. In order to evaluate the concentration of toxic metals (namely As, Cd, Co, Cr, Cu, Mn, Ni, Pb, Sb and Se), in crops and vegetable samples collected from the irrigated areas of Faisalabad and Gujranwala regions. Neutron activation analysis (NAA) and atomic absorption spectrometric (AAS) techniques have been used. All the observed metal concentrations were higher than the reported literature values. Moreover, the highest values of toxic metals of As (0.44±0.03 µg/g) and Co (0.5±0.01 µg/g), Mn (45.3±2.0 µg/g) and Sb (0.1±0.01 µg/g), Se (1.28±0.06 µg/g) and Pb (3.84±0.27 µg/g) were found in tomato, bitter gourd and rice samples respectively.